Achieving the cure of follicular lymphoma: is it time to finalize treatment strategies to reach this goal in a subset of patients? - Mauro Passucci; Giovanni Assanto; Alessandro Pulsoni (Mediterranean Journal of Hematology and Infectious Diseases)
NO ABSTRACT AVAILABLE